A literatura latino-americana e as alegorias nacionais de concierto Barroco - Caixeta, Maryllu Oliveira [UNESP] (Universidade Estadual de Maringa, 2011)
The problematical identity of Latin America is reflected on the recurrence of the theme in the literature created in this part of the continent. The images of Caliban and anthropophagy and the attribution of a Baroque meaning to the Latin American experience characterize an expressive part of such literature. By means of the character Amo, Carpentier's Concierto Barroco exemplifies the difficulties of the Creole elite in finding a nobleorigin for themselves in their ancestors' Europe, and in identifying themselves with it. The slave musician Filomeno and Amo naturalizes narrative, whereas Filomeno provocativelytransits between the hierarchies, turning the Baroque meaning of identity into an allegory. Jazz is a Creole, anthropophagic and Baroque product whose erased origin was replaced by the fabled narrative in the Spirituals that renewed modern music. It is important to emphasize that Carpentier created, by means of Filomeno, the unity of the American experience whose frontier is Mexico.
Latin-American Literature and national allegories present in the novella concierto Barroco
Keywords: Anthropophagy; Baroque; Latin-American literature